Decision Support System for Selecting KIP-K Recipients at Amikom University, Purwokerto Using the TOPSIS Method - Khotimah, Khusnul; Anggraini, Lintang Wahyu; Alfirnanda, Weersa Talta; Tahyudin, Imam (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2022)
The Indonesia Smart College Card Program (KIP-K) is a tuition assistance program (scholarship) from the Government through the Ministry of Education, Culture, Research and Technology (Kemdikbudristek). In the KIP-K scholarship selection process, criteria are needed to determine who is right to receive the KIP-K scholarship. This study aims to carry out the process of determining the ranking of KIP-K scholarship recipients based on the TOPSIS method. To determine scholarship recipients with outstanding achievements, Amikom Purwokerto University selects prospective scholarship recipients based on several criteria. The criteria used are Student DTKS Status, Parents' Income, Parents' Dependents, Average School Exams, Student Transportation Costs. The results obtained from this study are in the form of ranking obtained from the highest value to the lowest value. There were 112 prospective students who were entitled to get KIP-K scholarships out of a total of 314 applicants.